ANALISIS BAHAN AJAR AL-QARI AL-A'RABIY - Ahmad Rizki Nugrahawan; Amin Fauzi (Universitas Muhammadiyah Prof Dr Hamka, 2021)
This research aims to identify and to ensure the advisability of Arabic book module